Implementation of Covid-19 Budget Policy in Southeast Sulawesi (Case Study of Budget Refocussing and Reallocation of Regional Revenue and Expenditure Budgets 2020) - La Ode Muhammad Elwan; Abdul Kadir; Sitti Utami Rezkiawaty; Erni Qomariyah (Journal of Governance and Public Policy, 2023)
This study aims to examine and determine the COVID-19 Refocusing and Budget Reallocation Policy implementation in the Southeast Sulawesi Provincial Revenue and Expenditure Budget 2020. The research method used a qualitative approach with an analytical descriptive design. This research took place in Southeast Sulawesi. Primary and secondary data came from observations, interviews, and document studies. According to Miles-Huberman, data analysis techniques using an interactive analysis model included data in condensation, data presentation, and conclusion. The results showed that the COVID-19 Refocusing and Budget Reallocation Policy in Southeast Sulawesi, for the most part, could not be accounted for due to administrative errors and errors in the actions of the implementers and third parties. Based on Grindle's argument, the policy content seems to have been carried out too quickly, as evidenced by the 3 (three) changes to the COVID-19 budget. Based on indicators according to Van Meter and Horn, of the 6 (six) policy implementation indicators, only 1 (one) was fulfilled, so the implementation of the COVID-19 Refocusing and Budget Reallocation Policy in the Southeast Sulawesi Regional Revenue and Expenditure Budget 2020 is declared to have failed to meet the formulation and implementation of the policy.